Dwarfism in close continental amphibian populations despite lack of genetic isolation. Issue 8 (11th May 2020) - Hyeun‐Ji, Lee; Broggi, Juli; Sánchez‐Montes, Gregorio; Díaz‐Paniagua, Carmen; Gomez‐Mestre, Ivan
Abstract : Ample variation in body size is common in vertebrates over extensive geographical distances, or in isolated populations, where effective geographical barriers may cause dwarfism or gigantism. Here we study potential causes of extreme size reduction in continental populations of amphibians within a short geographical distance and in the absence of geographical barriers. Natterjack toads Epidalea calamita in Doñana National Park (Spain) experience up to 2.1‐fold difference in body mass in as little as 37 km. Studying six populations divergent in body size, we tested for genetic isolation of the dwarf populations using multilocus genotypes (16 microsatellites), and explored whether populations differ in trophic status (through stable isotope analysis), standard metabolic rate and growth pattern, senescence and age structure (conducting telomere length assays and skeletochronology). We also recorded advertisement calls across populations and experimentally tested for behavioural reinforcement of the body size variation through female preferences. Local dwarfism in these populations occurs in the absence of genetic isolation while maintaining relatively high effective population sizes. Dwarf populations, however, are exposed to drier and warmer climatic conditions, have different trophic status, show lower mass‐specific metabolic rate, and male advertisement calls with a higher dominant frequency. Juvenile growth differed among populations, reaching the adult stage at different body sizes. Altogether, our results suggest a significant influence of environmental conditions on the physiology and ecology of the Doñana E. calamita populations, mainly affecting toads between metamorphosis and sexual maturity. Further experimental and genomic studies focusing on these early life stages are necessary to dissect the relative roles of the environment and adaptive genetic differentiation on this phenomenon.